A novel way of responding to dissonance evoked by belief disconfirmation: making the wrongdoing of an opponent salient. (2nd January 2020) - Harmon-Jones, Eddie; Harmon-Jones, Cindy; Denson, Thomas F.
ABSTRACT: Based on dissonance theory, we predicted that individuals who supported a political figure (Donald Trump), were exposed to information about his wrongdoings, and believed the veracity of this information would be most likely to share social media that points to incidents in which opponents also engaged in wrongdoing. Participants ( N = 409) varying in their support for Trump were exposed to information concerning his alleged wrongdoings (or a neutral article). They viewed a meme of a political rival (Hilary Clinton) that alluded to her alleged wrongdoings, and reported how likely they would be to share the meme (and indicated how accurate they believed the Trump article was). Results supported the prediction, suggesting that dissonance may cause individuals to emphasize the wrongdoings of opponents.